Une éducation scientifique émancipatrice pour les élèves de maternelle et leur professeur - Joël Bisault (Recherches en Éducation)
In this paper, we propose to examine how scientific education can be emancipating for the pupils and the teacher. The actor’s ability of thinking by themselves is put ahead to consider in the same time emancipation of pupils and teacher. Emancipation’s indicators are definite for the pupils and tracks are suggested to conceive a teacher’s emancipation. School moments aiming on balloons are analyzed to illustrate this point of view.